Teachers’ experiences of using Learning Technology in Pakistan - Shah, Uzair; Hodgson, Vivien; Trehan, Kiran (Proceedings of the International Conference on Networked Learning, 2012)
Advancements in learning technology, such as computers, mobile devices and the Internet, have extended correspondence with faculty members, facilitated administrative activities and encouraged linkage and connections with other students beyond normal university office hours. Education technologists are exploiting the benefits of technology to transform teaching methods in universities and promote interaction and collaboration; aspects important to Networked Learning. Despite the extensive use of learning technology, limited research has been conducted to understand how faculty members experience use of learning technology within their pedagogical practices; and much of the existing literature is primarily located within the context of culturally western universities. This study aims to address this gap by illuminating the phenomenon of teachers’ experiences of using learning technology within their teaching practices at Hazara University (HU) located in Mansehra, Pakistan. Adopting an interpretivist paradigm, phenomenographic approach was used to understand and describe qualitatively different ways people perceive or view a particular phenomenon. The analysis elucidates five conceptions of using learning technology; these were identified as ’retaining attention’, ’professional skills development’, ’information enrichment’, ’connectivity’ and ’ omnipotential’. Retaining attention was described as the least complex; whereas the omnipotential category is relatively most sophisticated and is inclusive of other conceptions. The meanings (what aspects) of these categories are related to the how aspects or variations that are ’prior exposure of technology’, ’research-informed teaching’ and ’perceived scope of technological use’. The relationships between what and how aspects of the phenomenon of the use of learning technology, are summarized and presented in a tabular form. The paper suggests that to make a smoother transition into networked learning environments, academics may be better prepared to ’overcome the alienation and otherness of online spaces’ and be actively involved in networked learning environments when they experience learning technology onmipotentially. To further elaborate on this, omnipotential experience shall be analyzed using the framework of intentionality to better understand the conceptualization of the acts and their interrelated intent of the teachers that facilitate their meanings of omnipotential use of learning technology. This is an area which could prove insightful for future research in this field. The findings contribute to the extant literature and provide different ways of looking at learning technology by locating this research in a different cultural setting. This research offers new conceptions of learning technology within face-to-face pedagogical practices that may help guide the design of networked learning programmes and also course designs.